The Dynamic Relationship Between Social Support and HIV-Related Stigma in Rural Uganda - Takada, Sae; Weiser, Sheri D; Kumbakumba, Elias; Muzoora, Conrad; Martin, Jeffrey N; Hunt, Peter W; Haberer, Jessica E; Kawuma, Annet; Bangsberg, David R; Tsai, Alexander C (Springer, 2014)
Abstract Background Cross-sectional studies show that human immunodeficiency virus (HIV) stigma is negatively correlated with social support. Purpose The purpose of this study is to examine the bidirectional relationship between social support and HIV stigma. Methods We collected quarterly data from a cohort of 422 people living with HIV in Uganda, followed for a median of 2.1 years. We used multilevel regression to model the contemporaneous and 3-month-lagged associations between social support and both enacted and internalized stigma. Results Lagged enacted stigma was negatively correlated with emotional and instrumental social support, and lagged instrumental social support was negatively correlated with enacted stigma. Internalized stigma and emotional social support had reciprocal lagged associations. Conclusions Interventions to reduce enacted stigma may strengthen social support for people living with HIV. Improved social support may in turn have a protective influence against future enacted and internalized stigma.
Keywords: HIV/AIDS; Stigma; Social support; Uganda